Occipital Epileptiform Discharges and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The frequency of different causes of occipital epileptiform discharges (OEDs) and EEG features predictive of epilepsy type and outcome were analyzed in 90 children with OEDs examined at the Floating Hospital for Children, Tufts University School of Medicine, Boston, MA.